Medication utilization pattern among outpatients during the Hajj mass gathering - Saber Yezli; Sabra Zaraa; Yara Yassin; Abdulaziz Mushi; Andy Stergachis; Anas Khan (Elsevier, 2020)
Background: The Kingdom of Saudi Arabia (KSA) provides free healthcare, including medications, for the over 2 million Muslim pilgrims who attend Hajj every year. Information on drug utilization patterns at the Hajj is important to strengthen the supply chain for medicines, avert stock-outs, identify inappropriate use, and support public health planning for the event. Method: We investigated drug utilization pattern among outpatients in eight seasonal Holy sites hospitals in Makkah, KSA, during the 2018 Hajj. Data on medication prescribed and dispensed were retrieved from the hospitals' electronic records. Data were also used to calculate six of the WHO indicators for drug use at these facilities. Results: A total of 99,117 medications were prescribed for 37,367 outpatients during 37,933 encounters. Outpatients were mainly older males and originated from 134 countries. Twenty medications accounted for 72.8% of the 323 different medications prescribed. These were mainly nonsteroidal anti-inflammatory drugs, analgesics and antipyretics, and antibacterial medicines for systemic use. Outpatients were prescribed an average of 2.6 (SD = 1.2) drugs per consultation and polypharmacy (≥5 medications) was observed in 4.8% of the encounters. Antibiotics and an injection were prescribed in 46.9% and 6.5% of encounters, respectively. Nearly 90% of the prescribed drugs were actually dispensed. On average, medications were dispensed 16.4 (SD = 119.8) minutes from the time they were prescribed for the patient. All hospitals had a copy of the essential drugs list available and all of the prescribed drugs appeared on that list. Conclusion: Nonsteroidal anti-inflammatory drugs, analgesics and antibiotics are the most common medications prescribed to outpatient during Hajj. Our results, including the calculated WHO drug use indicators, can form a basis for further investigations into appropriate drug use at the Hajj and for planning purposes. These results could also guide the development of reference values for medications prescribing and use indicators at mass gatherings.